Aplikasi Analisis Sentimen Komentar Pengguna Genshin Impact Di Play Store - Muhammad Farras; Viny Christanti Mawardi; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Google Play functions as the official app store for the Android operating system, allowing users to browse and discover applications developed with the Android software development kit (SDK) and published through Google. Google Play also serves as a digital media store, offering music programs, books, movies, and television shows. It previously offered Google hardware for purchase until it introduced a separate online hardware store, Google Store, on March 11, 2015.The research will utilize a web-based application development tool that uses Flask and JavaScript as the application interface, and the Pandas library from Python for data manipulation. Naïve Bayes will be employed as the methodology for analyzing sentiments based on words, and K-Fold Cross Validation will be used to strengthen the accuracy of the analysis results.Sentiment analysis typically classifies opinions into three categories: positive and negative. However, applications that can perform the process of creating training and testing sets from consumer opinion data, simultaneously analyzing consumer sentiment and dynamically measuring the accuracy of the analysis results, are still scarce. This study aims to develop an application capable of analyzing consumer sentiment with the mentioned functionalities, wherein Naive Bayes is used as the classification method.